Pack Hike Test finishing time for Australian firefighters: Pass rates and correlates of performance - Phillips, M.; Petersen, A.; Abbiss, C.; Netto, Kevin; Payne, W.; Nichols, D.; Aisbett, B. (Elsevier, 2011)
The pack hike test (PHT, 4.83 km hike wearing a 20.4-kg load) was devised to determine the job readiness of USA wildland firefighters. This study measured PHT performance in a sample of Australian firefighters who currently perform the PHT (career land management firefighters, LMFF) and those who do not (suburban/regional volunteer firefighters, VFF). The study also investigated the relationships between firefighters' PHT performance and their performance across a range of fitness tests for both groups. Twenty LMFF and eighteen age-, body mass-, and height-matched VFF attempted the PHT, and a series of muscular endurance, power, strength and cardiorespiratory fitness tests. Bivariate correlations between the participants' PHT finishing time and their performance in a suite of different fitness tests were determined using Pearson's product moment correlation coefficient. The mean PHT finishing time for LMFF (42.2 ± 2.8 min) was 9 ± 14% faster (p = 0.001) than for VFF (46.1 ± 3.6 min). The pass rate (the percentage of participants who completed the PHT in under 45 min) for LMFF (90%) was greater than that of VFF (39%, p = 0.001). For LMFF, VO(2peak) in L min(-1)(r = -0.66, p = 0.001) and the duration they could sustain a grip 'force' of 25 kg (r = -0.69, p = 0.001) were strongly correlated with PHT finishing time. For VFF, VO(2peak) in mL kg(-1) min(-1)(r = -0.75, p = 0.002) and the duration they could hold a 1.2-m bar attached to 45.5 kg in a 'hose spray position' (r = -0.69, p = 0.004) were strongly correlated with PHT finishing time. This study shows that PHT fitness-screening could severely limit the number of VFF eligible for duty, compromising workforce numbers and highlights the need for specific and valid firefighter fitness standards. The results also demonstrate the strong relationships between PHT performance and firefighters' cardiorespiratory fitness and local muscular endurance. Those preparing for the PHT should focus their training on these fitness components in the weeks and months prior to undertaking the PHT.